Approaching an ergonomic future: An affordance-based interaction concept for digital human models - Wolf, Alexander; Krüger, Daniel; Miehling, Jörg; Wartzack, Sandro (Procedia CIRP Volume 84, 2019)
Digital human models offer great potential for the evaluation of physical human factors throughout all phases of product development. Unfortunately, digital human models lack a generic user-product interaction model to use them as universal and truly predictive CAE tools. In this contribution, we propose a concept for a generic and integrated interaction model based on the concept of affordances, the technology of CAD features and posture- and movement-prediction methods. Furthermore, we propose an affordance taxonomy, which shall enable a universal methodical description of interactions occurring during product us
Keywords: user-centered design; user-product interaction; digital human models; affordances; CAD features; human factors